Comparative Experimental Infection Study in Dogs with Ehrlichia canis, E. chaffeensis, Anaplasma platys and A. phagocytophilum - Nair, Arathy D.S.; Cheng, C.; Ganta, Chanran K.; Sanderson, Michael W.; Alleman, A. R.; Munderloh, U. G.; Ganta, Roman R. (My University, 2016)
Dogs acquire infections with the Anaplasmataceae family pathogens, E. canis, E. chaffeensis, E. ewingii, A. platys and A. phagocytophilum mostly during summer months when ticks are actively feeding on animals. These pathogens are also identified as causing diseases in people. Despite the long history of tick-borne diseases in dogs, much remains to be defined pertaining to the clinical and pathological outcomes of infections with these pathogens. In the current study, we performed experimental infections in dogs with E. canis, E. chaffeensis, A. platys and A. phagocytophilum. Animals were monitored for 42 days to evaluate infection-specific clinical, hematological and pathological differences. All four pathogens caused systemic persistent infections detectible throughout the 6 weeks of infection assessment. Fever was frequently detected in animals infected with E. canis, E. chaffeensis, and A. platys, but not in dogs infected with A. phagocytophilum. Hematological differences were evident in all four infected groups, although significant overlap existed between the groups. A marked reduction in packed cell volume that correlated with reduced erythrocytes and hemoglobin was observed only in E. canis infected animals. A decline in platelet numbers was common with E. canis, A. platys and A. phagocytophilum infections. Histopathological lesions in lung, liver and spleen were observed in all four groups of infected dogs; infection with E. canis had the highest pathological scores, followed by E. chaffeensis, then A. platys and A. phagocytophilum. All four pathogens induced IgG responses starting on day 7 post infection, which was predominantly comprised of IgG2 subclass antibodies. This is the first detailed investigation comparing the infection progression and host responses in dogs after inoculation with four pathogens belonging to the Anaplasmataceae family. The study revealed a significant overlap in clinical, hematological and pathological changes resulting from the infections.
Citation: Nair, A. D. S., Cheng, C., Ganta, C. K., Sanderson, M. W., Alleman, A. R., Munderloh, U. G., & Ganta, R. R. (2016). Comparative Experimental Infection Study in Dogs with Ehrlichia canis, E. chaffeensis, Anaplasma platys and A. phagocytophilum. Plos One, 11(2), 21. doi:10.1371/journal.pone.0148239
Keywords: Serum Antiplatelet Antibodies; Monocytic Ehrlichiosis; Cyclic; Thrombocytopenia; Humoral Immunity; Nested Pcr